The Effect of Polysulphated Glycosaminoglycan on the Production of Proteoglycan by Equine Tendon Fibroblasts in Monolayer Culture - Dahlgren, Linda A.; Rosenbusch, R. F.; Booth, L. C. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Equine tendon fibroblasts were isolated from tissue fragments of superficial digital flexor tendon, subcultured and maintained in monolayers. The cells were treated with two dosage regimes of polysulphated glycosaminoglycan (PSGAG). The high dose group received 0,25, 50 or 200 μg/ml of PSGAG and the low dose group received 0,0.3,1 or 2 μg/ml of PSGAG. Proteoglycan production was measured via liquid scintillation counting, following radiolabel with 35SO4 (40 μCi/ml). The counts were measured in both the cell associated fraction and the supernatant fraction.The addition of PSGAG to the culture system did not adversely affect cell viability at any treatment level. The cells in all of treatment groups produced measurable amounts of proteoglycan in both the cell associated and supernatant fractions. There were not any differences between the treatment means in any of the four groups (high dose cell-associated, high dose supernatant, low dose cell-associated, low dose supernatant). A linear trend in proteoglycan production was not documented between treatment groups in either the cell-associated or the supernatant fractions for either of the two dosage regimes. The significance of the lack of effect is equivocal. PSGAG may influence tendon healing in a manner other than by increasing proteoglycan production.The effect of polysulphated glycosaminoglycan on the production of proteoglycans by equine tendon fibroblasts was investigated. A previously described model was utilized to grow the tendon fibroblasts in monolayer cultures. Significant treatment effects were not seen at either a high or low dose of PSGAG. Addition of the PSGAG did not adversely affect cell viability at any treatment level.
Keywords: Tendinitis; polysulphated glycosaminoglycan